EKOKRITIK SASTRA DALAM PUISI TALANG DI LANGIT FALASTIN KARYA DHENI KURNIA - Aris, Qori Islami (Jurnal Ilmu Budaya, 2020)
One of the literary works is poetry. Poetry can be a medium for poets to convey ideas, concepts and thoughts. One of these ideas and thoughts is based on the observations of the environment. It implies that poetry is also related to other fields of study. One of the fields of study that can be related to literary works is ecocriticism. Ecocritics is focused on the relationship between literature and the environment or how the relationship between humans and their physical world are reflected in literary works. In this study, the writer tries to analyze the poetry Talang di Langit Falastin written by Dheni Kurnia through the concept of echocritics as an analytical lens. The result of this study shows that Talang di Langit Falastin illustrates environmental exploitation and pollution caused by political and economic factors. This poem becomes interesting because the poet analogized Talang Mamak and Palestine which are equally oppressed, causing environmental destruction and exploitation. The destruction of the environment in Palestine was caused by the Zionist invaders who bombarded with bombs and nuclear weapons, while the environmental destruction in Talang Mamak was carried out by capitalists who burned forests to open the new land for economic interests that affected the misery of living things in the environment.